2016
DOI: 10.1590/0001-3765201620160123
|View full text |Cite
|
Sign up to set email alerts
|

Nasal carriage of resistant Staphylococcus aureus in a medical student community

Abstract: Staphylococcus aureus can cause a variety of infections due to its high transmissibility, high pathogenic potential and resistance to multiple drugs, factors that contribute to the relevance of infections in healthcare services. The aim of this study was to document phenotypic and genotypic resistance factors of Staphylococcus aureus strains, isolated from nasal mucosa of medical students. A nasal swab was collected from the nares (nostrils) of 222 medical students. After collection, the samples were submitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 18 publications
(7 reference statements)
0
6
0
Order By: Relevance
“…In this study, the resistance rate of erythromycin (73.5%, Table 1 ) was higher than that in Belgium (37.4%) [ 20 ], Iran (42%) [ 21 ] and India (51.7%) [ 22 ], but lower than that in Korean (77.5%) [ 23 ] and Brazil (95.2%) [ 24 ]. Interestingly, compared with two previous reports (97.3% in MSSA, 98% in MRSA and 59.1% in S. aureus ) [ 25 , 26 ] surveyed in China, our study indicated different geographical regions and bacteria sources harbored diverse but increasing erythromycin resistant ratio.…”
Section: Discussionmentioning
confidence: 62%
See 1 more Smart Citation
“…In this study, the resistance rate of erythromycin (73.5%, Table 1 ) was higher than that in Belgium (37.4%) [ 20 ], Iran (42%) [ 21 ] and India (51.7%) [ 22 ], but lower than that in Korean (77.5%) [ 23 ] and Brazil (95.2%) [ 24 ]. Interestingly, compared with two previous reports (97.3% in MSSA, 98% in MRSA and 59.1% in S. aureus ) [ 25 , 26 ] surveyed in China, our study indicated different geographical regions and bacteria sources harbored diverse but increasing erythromycin resistant ratio.…”
Section: Discussionmentioning
confidence: 62%
“…It is notable that the predominance of these genes (i.g. ermA and ermC ) was variable in several countries [ 4 , 24 , 29 31 ]. Here in China we found that, among the 27 macrolide-resistant S. aureus isolates, ermC was the most prevalent resistance determinant and ermA was less prevalent (51.9% vs 11.1%, Table 3 ).…”
Section: Discussionmentioning
confidence: 99%
“…In addition, the analogous report that the detection rate of S. aureus at Wenzhou Medical College in Wenzhou was 15.4%, of which 3.0% were MRSA [29]. Besides, the study from Brasil reported that in a medical student community, the detection rate of S. aureus and MRSA were 20.6 and 3.4% [30]. In contrast, the detection rate of S. aureus in this study is higher than the analogous report, but the detection rate of MRSA is lower.…”
Section: Discussionmentioning
confidence: 99%
“…Cotton swabs (Yangsheng Biotech, PR China) were used to collect samples from anterior nares of hospital personnel. The cotton swab was gently inserted into one of the nostrils up to 1 cm and was rotated three times to sample the inner surfaces [5]. Hand samples were collected using sterile phosphate-buffered saline (PBS) buffer-soaked cotton swabs.…”
Section: Methodsmentioning
confidence: 99%